PEMETAAN PERSEPTUAL KONSUMEN KAIN TENUN SASAK MENGGUNAKAN METODE MULTIDIMENSIONAL SCALING - Handayani Rinuastuti; Lalu Suparman; Thatok Asmony (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
In the Sasak tribe, the existence of woven cloth has a very important position, however, this craft is currently increasingly difficult to survive amid woven products from outside the region that flood outlets both in tourist and trade areas. On the other hand, tourists or consumers who buy woven fabric products often cannot distinguish between Sasak weaving and woven fabrics from other regions, even between the woven fabrics produced from one village to another. As a result, Sasak weaving becomes difficult to compete. Therefore, Sasak weaving needs to be introduced to its quality and uniqueness compared to weaving from other regions, even the peculiarities of weaving from one village to another. Therefore, scientific study and analysis is needed, so as to provide a more precise solution that aims to map consumer perceptions through Multi Dimensional Scaling Analysis (MDS). This study involved 103 respondents who know about the woven fabrics Sukarara, Sade and Pringgasela. The MDS results show that the Sukarara cloth is considered very different from the Pringgasela, while the Sade woven cloth has similarities with the Sukarara and Pringgasela woven fabrics. There are two attributes that characterize the woven fabrics of the Sasak tribe, namely easy maintenance and bright colors, but they have different perceptions on several other attributes.